THE PROBLEMS OF ASSESSING THE EFFECTIVENESS OF THE INDIVIDUAL-ACCRUAL MODEL OF PENSION INSURANCE - A. K. Solov’ev (Финансы: теория и практика, 2018)
Topic. The article presents the results of actuarial analysis of the newest and most controversial component of the Russian system of compulsory pension insurance — accrual one. The prospect of its further development is estimated. The effectiveness of this method of pension provision is assessed by the author from the point of view the role and degree of performance of the institutional functions of the state pension system (i.e., ensuring a decent level of material security of pensioners), and the possibility of achieving the targets formulated in 2012 in the government’s Strategy for the long-term development of the pension system of the Russian Federation.Purpose. Development of economically reasoned justification of real financial relations between participants of the insurance pension system within the framework of individual-accrual models of pension provision.Methodology. The main methodological feature and originality of this study is a multi-factor analysis, using methods of comparative analysis and actuarial forecasting of the whole set of conditions for the formation and implementation by insured persons of their pension rights in the individual-accrual model (both external to the pension system and internal as well), not carried out in other studies on this problem.Results.The article presents the results of economicstudies of the national practice of formation and implementation of pension rights of workers in the framework of the individual-accrual pension insurance program. Those results can be used in substantiating the directions of reforming the accrual methods of pension provision:The degree of direct dependence of the pension system efficiency on external macroeconomic and demographic factors is proved.We formulated criteria for evaluating the effectiveness of the accrual component of the pension system.It is given the characteristic and the main tasks of the accrual component of the compulsory pension insurance system.There are proposed measures to improve the functioning of the accrual component in the existing Russian reality and in the long term.Conclusions. The accrual method of formation and realization of pension rights in specific long-term socioeconomic conditions does not allow the main categories of insured persons to form the level of pensions provided in the solidarity system, and also sharply increases the budgetary risks not only of the Russian Pension Fund (PFR), but also of the Federal budget.